Método de caracterização do sombreamento de espaços públicos abertos gerado por edificações no entorno - Pinto, Jeanne Moro Moreira (2019)
Most Brazilian cities are undergoing a period of marked urbanization, increasing the urban density and the building height, changing the amount of solar access incident in public spaces. The objective of this work is to develop a method for analyzing, , from satellite images, the impact of shading from surroundings buildings on open public spaces, in order to assist and provide subsidies from the urban planning stage, in view of the search for more qualitative results for the well-being of all the inhabitants of the city. Integrating open data, spatial data manipulation and simulation tools, for the proposed method validation shading estimates were made in different spaces in the city of Curitiba/PR, on winter and summer solstices, and spring equinox. As part of the process, different methods were also studied to obtain buildings height, one of them being developed in this work. Different types of spaces were analyzed for the current configuration of surroundings buildings and considering a future scenario, selected from three criteria: buildings height, amount of vegetation, and number of existing seats in each space. Results were observed through visualization maps and quantitative data. The analyses of the spaces with the current configuration of surrounding buildings showed that, in the winter solstice, 8% of the analyzed spaces had more than 50% of their shaded area with shading overt a period of between three and five hours. On the other hand, the analysis of future scenarios has shown that the study of the construction of new buildings around open public spaces is important and necessary, especially when vertical growth is allowed in cities such as Curitiba, characterized by cold weather in winter, when solar access is largely recommended. The method, object of this Thesis, proved to be applicable and reliable, and can be useful from the initial stages of urban planning, as well as for readjustments of existing spaces, and as a tool to analyze the impact of new constructions of surrounding buildings, or even in study of boundary height parameters of buildings around these sites.